2008
DOI: 10.1016/j.cognition.2007.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Intersensory redundancy accelerates preverbal numerical competence

Abstract: Intersensory redundancy can facilitate animal and human behavior in areas as diverse as rhythm discrimination, signal detection, orienting responses, maternal call learning, and associative learning. In the realm of numerical development, infants show similar sensitivity to numerical differences in both the visual and auditory modalities. Using a habituation-dishabituation paradigm, we ask here whether providing redundant, multisensory numerical information allows six-month-old infants to make more precise num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
68
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 27 publications
10
68
2
Order By: Relevance
“…Thus, rather than number being detected as a last resort, it seems more likely that infants simultaneously track the number of discrete objects in a set and the non-numerical characteristics of those objects. Consistent with this interpretation, combining auditory and visual cues to number improves the Weber-Fechner ratio that infants can discriminate over that which they can discriminate on the basis of visual cues alone (Jordan, Suanda, & Brannon, 2008). …”
supporting
confidence: 60%
“…Thus, rather than number being detected as a last resort, it seems more likely that infants simultaneously track the number of discrete objects in a set and the non-numerical characteristics of those objects. Consistent with this interpretation, combining auditory and visual cues to number improves the Weber-Fechner ratio that infants can discriminate over that which they can discriminate on the basis of visual cues alone (Jordan, Suanda, & Brannon, 2008). …”
supporting
confidence: 60%
“…Research on infant numerical cognition has consistently shown that providing infants with multiple cues boosts their sensitivity to numerical differences (Jordan, Suanda, & Brannon, 2008) as well as their ability to extract ordinal numerical relations (Suanda, Tompson, & Brannon, 2008). Therefore, in Experiment 3 we tested a new group of 4-month-old infants using a new set of test stimuli, in which the magnitude difference between the with -OM and the against-OM sequences was provided not only by number, but also by cumulative surface area, as the two cues covaried one with the other between the sequences (the habituation stimuli for Experiment 3 remained identical to those in Experiment 2).…”
Section: Resultsmentioning
confidence: 99%
“…In the current experiment it was predicted, based on neuroimaging and ERP work with human adults (Alpert et al, 2008;Beauchamp et al, 2004;Calvert, 2001;Calvert et al, 2001;Kayser et al, 2007), single cell recordings in animals (see Stein, Meredith, & Wallace, 1994 for a review), and behavioral work with infants Jordan, Suanda, & Brannon, 2008), that the synchronous presentation of bimodal (auditoryvisual) stimulation would evoke an amplified auditory response compared to unimodal auditory stimulation in infants. A group of adults was also included to allow for a comparison of the infant ERP response to that of the mature ERP in response to the same stimuli.…”
Section: Introductionmentioning
confidence: 99%